Epistatic effects between amino acid insertions and substitutions mediate toxin-resistance of vertebrate Na+, K+-ATPases - ÖZBEK SARICA, PEMRA (My University, 2022)
The recurrent evolution of resistance to cardiotonic steroids (CTS) across diverse animals most frequently involves convergent amino-acid substitutions in the H1-H2 extracellular loop of Na+, K + -ATPase (NKA). Previous work revealed that hystricognath rodents (e.g. chinchilla) and pterocliform birds (sandgrouse) have convergently evolved amino-acid insertions in the H1-H2 loop, but their functional significance was not known. Using protein engineering, we show that these insertions have distinct effects on CTS resistance in homologs of each of the two species that strongly depend on intramolecular interactions with other residues. Removing the insertion in the chinchilla NKA unexpectedly increases CTS resistance and decreases NKA activity. In the sandgrouse NKA, the amino acid insertion and substitution Q111R both contribute to an augmented CTS resistance without compromising ATPase activity levels. Molecular docking simulations provide additional insight into the biophysical mechanisms responsible for the context-specific mutational effects on CTS insensitivity of the enzyme. Our results highlight the diversity of genetic substrates that underlie CTS insensitivity in vertebrate NKA and reveal how amino-acid insertions can alter the phenotypic effects of point mutations at key sites in the same protein domain.
Keywords: Kimya Mühendisliği ve Teknolojisi; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, KİMYASAL; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, CHEMICAL; Akışkan Akışı ve Transfer İşlemleri; Kolloid ve Yüzey Kimyası; Kimyasal Sağlık ve Güvenlik; Kataliz; Kimya Mühendisliği (çeşitli); Genel Kimya Mühendisliği; Fizik Bilimleri; Fluid Flow and Transfer Processes; Colloid and Surface Chemistry; Chemical Health and Safety; Catalysis; Chemical Engineering (miscellaneous); General Chemical Engineering; Physical Sciences; Na+ K+ -ATPase; cardiotonic steroids; chinchilla; sandgrouse; indel evolution.